The postgraduate relationship - Daing Nasir, Ibrahim (2013)
In life, there are several types of relationships. Marriage is the simplest example. The relationship can be good or otherwise. It can be nurtured or left to chance until its eventual outcome. For postgraduate research students, there is a relationship that comes with their research endeavour: the student-supervisor relationship.